Geochemical-mineralogical analysis of ferromanganese oxide precipitated on porifera in the Magellan seamount, western Pacific - Park, Kyuyoung; Jung, Jaewoo; Park, Jinsub; Ko, Youngtak; Lee, Yongmoon; Yang, Kiho (Frontiers in Marine Science, 2023)
This study investigated ferromanganese oxide (Fe-Mn oxide) precipitated on porifera located on the tabletop of the Magellan seamount (OSM17, 1571 m depth) in the western Pacific. As the growth rate of Fe-Mn oxide is several mm/Myr and porifera skeletons are difficult to preserve posthumously, geochemical and mineralogical studies have not yet been conducted on this topic. Fe-Mn oxides from porifera have a morphological differentiation from general ferromanganese deposits because porifera act as substrates for the Fe-Mn oxide. The thickness of Fe-Mn oxide cannot be visually confirmed because it thinly precipitates on the skeletons of porifera. Therefore, high-resolution fluctuations are reflected in marine environmental factors, such as redox conditions and surface productivity over tens of thousands of years, compared to ferromanganese deposits representing tens of millions of years. Hence, the geochemical and mineralogical characteristics were investigated. Porifera skeletons were confirmed, displaying a stratified lattice-like structure, thickness of Fe-Mn oxide of up to 110 μm, and age of approximately 55,000 years. Irregular distribution of major elements of Fe-Mn oxide, Mn, Fe, Ni, and Co was due to the characteristics of the structures. The presence of Fe-vernadite, identified by quantitative and mineralogical analysis, indicates oxidative environmental conditions at the tabletop of OSM17. Biomineralization was identified by confirming the presence of Fe-Mn oxides with a globular, sheath-like structure. Because of its conservation state, species identification of porifera was not based on the shape of the spicule, but was confirmed to be Farrea occa. This study verified that the tabletop of OSM17 has been in an oxidative environment for approximately 55,000 years, and through species identification, high dissolved silica (DSi) concentrations provide appropriate conditions for Farrea occa to survive. The sample in this study can be used as a new indicator in paleo-environment research.